MENJALIN HUBUNGAN SOSIAL MELALUI KESANTUNAN BERBAHASA - Yonsa, Yuliana Febri Yornai (sarasvati, 2020)
The culture of a society will be reflected in the politeness it implements, including politeness in language. The purpose of this article is to describe the strategies that can be used by the speaker and the interlocutor to achieve good communication, the types of politeness in language, and the ethics used in speaking and speaking. It can be concluded that there are many ethics, manners and courtesy in speaking that are known and adhered to by the communityÂ